Cluster-based approach utilizing optimally tuned TD-DFT to calculate absorption spectra of organic semiconductor thin films - Craciunescu, Luca; Asbach, Maximilian; Wirsing, Sara; Hammer, Sebastian; Unger, Frederik; Broch, Katharina; Schreiber, Frank; Witte, Gregor; Dreuw, Andreas; Tegeder, Petra; Fantuzzi, Felipe; Engels, Bernd (Journal of chemical theory and computation, 2023)
The photophysics of organic semiconductor (OSC) thin films or crystals has garnered significant attention in recent years since a comprehensive theoretical understanding of the various processes occurring upon photoexcitation is crucial for assessing the efficiency of OSC materials. To date, research in this area has relied on methods using Frenkel-Holstein Hamiltonians, calculations of the GW-Bethe-Salpeter equation with periodic boundaries, or cluster-based approaches using quantum chemical methods, with each of the three approaches having distinct advantages and disadvantages. In this work, we introduce an optimally tuned, range-separated time-dependent density functional theory approach to accurately reproduce the total and polarization-resolved absorption spectra of pentacene, tetracene, and perylene thin films, all representative OSC materials. Our approach achieves excellent agreement with experimental data (mostly ≤0.1 eV) when combined with the utilization of clusters comprising multiple monomers and a standard polarizable continuum model to simulate the thin-film environment. Our protocol therefore addresses a major drawback of cluster-based approaches and makes them attractive tools for OSC investigations. Its key advantages include its independence from external, system-specific fitting parameters and its straightforward application with well-known quantum chemical program codes. It demonstrates how chemical intuition can help to reduce computational cost and still arrive at chemically meaningful and almost quantitative results.